(untitled) (International Journal of Veterinary Medicine and Animal Science, 2024)
Ever since antibiotics were discovered for the treatment of bacterial diseases, an increase in antibiotic-resistant bacteria has been noticed as an economic and public health concern with a high rate of morbidity and mortality. Antibiotic resistance in broiler chickens can be a great threat to public health. This research aimed to screen commercial poultry’s gastrointestinal and respiratory tract bacteria to observe the antibiotic resistance pattern. In this experiment, gastrointestinal tract (GIT) and respiratory tract (RT) bacteria were identified using 16s rRNA gene sequencing from broiler chickens in anaerobic conditions following a bile salt tolerance assay and an antibiotic susceptibility test. Lactobacillus reuteri, Lactobacillus salivarius, and Enterococcus hirae were identified as the isolates. The bacteria found in the gut had a modest degree of bile salt tolerance. The isolates were sensitive to amoxicillin, gentamicin, and streptomycin but resistant to tetracycline, levofloxacin, metronidazole, azithromycin, and erythromycin. This study ensures that the GIT and RT of broiler chicken is a hidden source of the isolated bacteria. A large part of this bacterial population is antibiotic-resistant and reported as a public health concern.